Mengungkap Asihan dalam Manuskrip Awrād K.H. Sandra - Koyimah, Koyimah; Al Ayubi, Sholahuddin; Sugito, Mohamad Shofin; Wardah, Eva Syarifah; Hidayat, Angga Pusaka (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
Banten is one of the regions that houses a rich collection of magical manuscripts. In the Ciomas District, the Awrād manuscript of K.H. Sandra was unearthed, containing segments with magical teachings. This study aims to achieve two primary objectives: first, to identify Awrād manuscripts, and second, to contextualize these manuscripts within the lives of the Bantenese people. The research employs philological methods, encompassing manuscript inventory, description, transliteration, text editing, translation, and contextual analysis. The findings indicate that K.H. Sandra’s Awrād manuscript is a singular text, thus subjected to a standardized textual criticism process. Various errors such as omission, addition, and substitution are found in the process of textual criticism. This manuscript underscores that magical practices are deeply ingrained in the social fabric of Bantenese society, particularly in addressing challenges perceived as insurmountable through rational means. The Awrād manuscript serves as compelling evidence of the community’s steadfast belief in magical potency. These practices are not confined to social rituals but are also intertwined with religious life. This research underscores the necessity of preserving and further investigating similar manuscripts to gain a deeper understanding of Bantenese cultural heritage and magical traditions.